In vitro establishment, validation and characterisation of conjunctival epithelium outgrowth using tissue fragments and amniotic membrane. Issue 3 (9th June 2021) - Bertolin, Marina; Barbaro, Vanessa; Breda, Claudia; Ferrari, Stefano; Marchini, Giorgio; Pedrotti, Emilio; Ferrari, Barbara; Diego, Ponzin; Fasolo, Adriano
Abstract : Background/Aims: To set up the in vitro conditions for renewal of the conjunctival epithelium using healthy fragments of conjunctival tissue glued over an amniotic membrane. Methods: We evaluated the capability of conjunctival tissue fragments to generate conjunctival cell outgrowth after seeding them onto amniotic membrane and culture plates; we then assessed conjunctival molecular marker expression by immunofluorescence. We also evaluated the efficiency of glueing the fragments over the amniotic membrane to determine the best setting and the feasibility of shipping preloaded amniotic membranes. Results: Epithelial outgrowth was detected in 65%–80% of conjunctival fragments starting 48–72 hours after glueing, without major differences between type of membrane preparation and fragment size. Within 6–13 days, a full epithelium covered the surface of the amniotic membrane. Specific marker expression (conjunctival epithelium, Muc1, K19, K13; stemness, p63; tight junctions, ZO-1) was detected. Results of the shipping test showed that only 31% of the fragments were still glued over the epithelial side of the membrane within 24 hours compared to more than 90% of fragments stayed attached in the remaining conditions. Conclusion: The in vitro regeneration of conjunctival epithelium following outgrowth from conjunctival tissue fragments glued over an amniotic membrane may offer a viable strategy to renew the epithelium in vivo once applied over the ocular surface at the recipient site.